Pembiasaan Salam-Senyum-Sapa (3S) dalam Penguatan Pendidikan Karakter Kesopanan Anak Usia 4-5 Tahun di KB Aisyah Rahman - Tri Kusniawati; Moch Maulana Trianggono; Eka Olivia Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education in early childhood is an essential foundation for developing children’s behavior and social attitudes. One form of strengthening character education that can be implemented in the school environment is through the habituation of Greeting, Smiling, and Saluting (3S). This habituation aims to instill politeness, respect, and courteous social interaction skills from an early age. This study aims to describe the implementation of the Greeting–Smiling–Saluting (3S) habituation in strengthening the politeness character education of children aged 4–5 years at KB Aisyah Rahman. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of the principal, teachers, and children aged 4–5 years. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while data validity was tested through source triangulation and technique triangulation. The results of the study indicate that the 3S habituation was implemented through daily routine activities, teacher role modeling, reinforcement of positive behavior, and integration into learning activities and children’s social interactions at school. The implementation of this habituation contributed positively to the development of children’s politeness character, such as the ability to greet politely, respect teachers and peers, communicate courteously, and demonstrate polite behavior in daily life. Supporting factors for the success of the 3S habituation included teacher commitment, a conducive school culture, and parental support, while inhibiting factors included differences in family backgrounds and the lack of consistency in habituation at home. Therefore, the Greeting–Smiling–Saluting (3S) habituation is considered effective as a strategy for strengthening politeness character education in early childhood.